A Measurement of Aggregate Trade Restrictions and their Economic Effects - Estefania-Flores, Julia (IMF Working Papers; Working Paper ;, 2022)
We develop a new Measure of Aggregate Trade Restrictions (MATR) using data from the IMF's Annual Report on Exchange Arrangements and Exchange Restrictions. MATR is an empirical measure of how restrictive official government policy is towards the international flow of goods and services. MATR is simple, ad hoc, plausible, quantitative, easily updated, based solely on policy-relevant measures of trade policy, and covers an unbalanced sample of up to 157 countries annually between 1949 and 2019. MATR is strongly correlated with, but more comprehensive than, existing measures of openness and trade policy existing measures. We use MATR to show that trade restrictions are harmful for the economy and lead to significant contractions in output.